The role of business processes in influencing the decision support capabilities of enterprise content management system (ECMS): towards a framework - Mohamad Rahimi Mohamad Rosman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Facing an unprecedented explosion of digital content, many organisations have been left with a large repository of unstructured information. Huge volumes of electronic content have been captured and stored within organisations’ repositories, depriving organisations of the ability to analyse this data properly. As a result, many organisations are facing crucial problems, such as (1) employees wasting 30% of their time looking for relevant information; (2) operational and maintenance cost increases to handle large amounts of data; and (3) loss of opportunities to gain a strategic advantage through proper analysis of organisational data. To overcome these problems, the Enterprise Content Management System (ECMS) was introduced in the early 2000s. Having been researched for a period of 25 years, most prior studies on ECMS focus on a bottom-up approach with the intention of achieving immediate benefits such as cost-reduction, meaningful knowledge work and re-use of previous content. A top-down approach that aims to improve decision-making, resource allocation and competitive intelligence are ignored due to a lack of awareness about the importance of such benefits. Therefore, this research will explore the relationship between ECMS and how it can facilitate decision-making processes. Grounded on previous literature, the contributions of this paper are as follows: first, the paper provides insight into the research from the perspective of ECMS; second, the paper proposes a research model for further exploration of the topic; finally, implications and future directions for research is outlined.